DESIGN AND DECOUPLING OPTIMIZATION OF MAGNETORHEOLOGICAL ENGINE SUSPENSION SYSTEM - SHEN YuRui; FANG CongMin; WANG NingNing; YANG YuPing; LIU XinHua (Jixie qiangdu)
The engine suspension device based on magnetorheological fluid is designed,and the magnetic field simulation is performed by using Ansoft Maxwell. The vibration reduction principle of powertrain suspension system is presented and analyze its dynamics. The decoupling calculation model of magnetorheological suspension system is established, and the structural parameters of magnetorheological suspension system are optimized by fruit fly optimization algorithm.